2021
DOI: 10.3389/fpsyt.2021.712670
|View full text |Cite
|
Sign up to set email alerts
|

The Schoolteachers' Version of the Stress and Anxiety to Viral Epidemics-9 (SAVE-9) Scale for Assessing Stress and Anxiety During the COVID-19 Pandemic

Abstract: This study aimed to validate the schoolteachers' version of the Stress and Anxiety to Viral Epidemics-9 (SAVE-9) scale. This scale assessed the work-related stress and anxiety response of schoolteachers to the COVID-19 pandemic. A total of 400 schoolteachers participated in an online survey between March 4 and 15, 2021. The survey questionnaire included the schoolteachers' version of the SAVE-9, Patient Health Questionnaire-9 (PHQ-9), and Generalized Anxiety Disorders-7 (GAD-7) scales. A scree test and paralle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…28 Similar results were also reported among schoolteachers. 48 Additionally, it has been noted that public servants' anxiety is highly correlated with depression and resilience mediated the association between stress, anxiety, and depression during the nonpandemic years. 27 Consequently, anxiety reaction, regardless of whether it was derived from the viral pandemic or not, contributes to depression and resilience acts as a mediator between them in case of public workers.…”
Section: Viral Anxiety Depression and Resilience Of Public Workers Du...mentioning
confidence: 99%
“…28 Similar results were also reported among schoolteachers. 48 Additionally, it has been noted that public servants' anxiety is highly correlated with depression and resilience mediated the association between stress, anxiety, and depression during the nonpandemic years. 27 Consequently, anxiety reaction, regardless of whether it was derived from the viral pandemic or not, contributes to depression and resilience acts as a mediator between them in case of public workers.…”
Section: Viral Anxiety Depression and Resilience Of Public Workers Du...mentioning
confidence: 99%
“…Anxiety-related psychological problems were assessed on the Likert-4 scale, with options ranging from “totally uncertain = 0,” “a few days =1,” “more than half the time = 2,” and “almost every day =3” on a scale of 0 to 21. The threshold of anxiety was set to higher than 5 based on the Gad-7 score ( Ahn et al, 2021 ; Park et al, 2021 ; Yoo et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Female teachers face twice as much anxiety compared to their male counterparts (Lizana & Lera, 2022). This is because they had to balance between their family affairs and work affairs (Desouky & Allam, 2017;Atabek et al, 2019;Budyawati & Utami, 2019;Dizon-Ross et al, 2019;Ng et al, 2019;Othman & Sivasubramaniam, 2019;Bete et al, 2020;Li et al, 2020;Ratanasiripong et al, 2020;Ozamiz et al, 2021;Santamaría et al, 2021;Lizana et al, 2021;Wakui et al, 2021;Yoo et al, 2021;Gawrych et al, 2022;Spadafora et al, 2022). Jakubowski & Sitko (2021) in their study found that female teachers in Poland are more likely to have anxiety and depression as the culture of the country still associates managing household to be a full responsibility of a female.…”
Section: Independent Factormentioning
confidence: 97%
“…Identify the trend of research on anxiety and depression among teachers according to the year of publication approach and national context. Ratanasiripong et al, 2021;Santamaría et al, 2021;Wong et al, 2021;Wakui et al, 2021;Yoo et al, 2021;Bete et al, 2022;Gawrych et al, 2022;Lizana et al, 2022;Spadafora et al, 2022). 4 shows 5 sub-factors from work that lead to anxiety and depression of a teacher.…”
Section: Findings Findings Based On First Research Objectivementioning
confidence: 99%